Using geolympus to create a pervasive game experience in the higher education context - Arango-López, Jeferson (2021)
The number of game experiences based on the player’s location has increased recently due to proliferation of and innovation in related technologies. In the educational context, the goal of these games has been to increase the player’s skills with respect to a particular topic. When pervasive or narrative components are added; however, complexity of construction and support increases, requiring a tool to manage the information both appropriately and dynamically. Space and pervasiveness of social interaction work together to achieve objectives through the exchange of information between several pervasive games to provide a better game experience. This paper presents a platform enabled to create game experiences based on the player’s location to improve students’ skills by applying the pervasive narrative. It then validates a game experience designed and built in a higher education environment.